Bellevalia iranica (Asparagaceae, Scilloideae), a new species from Iran - Ali̇pour Sajad; Maji̇di̇ Rami̇ar; Eker İsmai̇l (Phytotaxa, 2025)
A new species, Bellevalia iranica Alipour, Eker, & Majidi (Asparagaceae) from Iran, is described and illustrated. It is superficially similar to B. cyanopoda, but differs from it mainly in: shape and size of the flowers, the length of the pedicels, and the non-elongating scape in fruit, shape and size of the capsules, the length of leaves, and the shape of raceme as well as altitude and flowering period characteristics. Also, it is partly similar to B. shiraziana, but differs from it mainly in: color of outer tunic, number of leaves, number of flowers in the raceme and raceme size, short pedicels, the shape, color and size of flowers, size and color of lobes. A comprehensive description, diagnostic characters, original photographs, geographical distribution, conservation assessment, and taxonomic comments on the new species are presented.